Pelatihan Pembuatan Lembar Kerja Variatif secara Mandiri untuk Guru Paud Prada Aulia - Andrian Andrian; Khairil Anwar; Nurianti Sitorus; Ika Agustina; Juwairiah Juwairiah; Yusnia Sinambela (Jurnal Pengabdian Masyarakat, 2025)
The training on the independent development of varied worksheets for teachers at PAUD Prada Aulia aims to enhance teachers’ competencies in designing creative, contextual, and developmentally appropriate learning media for early childhood education. Worksheets serve as an important tool in supporting meaningful learning processes; however, many teachers still rely on ready-made teaching materials that are often not aligned with the specific needs of learners. This program employed several methods, including material presentation, demonstrations, hands-on practice, and mentoring in the development of varied worksheets. The results of the training indicate an improvement in teachers’ understanding and skills in creating innovative and engaging worksheets that are aligned with early childhood learning objectives. Furthermore, teachers became more independent and confident in developing their own instructional materials. This training is expected to have a positive impact on the quality of learning in early childhood education and to encourage teachers to continuously innovate in creating effective and enjoyable learning media.